2022
DOI: 10.1111/imr.13159
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as immune effector cells in antibody therapy in cancer

Abstract: Over the last decades, new therapies have greatly improved the treatment of different cancer types. For example, immunotherapy is the collective of therapies that aims to recruit and stimulate the patient's own immune system to eradicate the tumor. 1 The tumor microenvironment (TME) comprises a great variety of cells, including endothelial cells, fibroblasts, and immune cells. Immune cells in the TME play a crucial role during cancer progression. Via immunosurveillance, immune cells are able to identify and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 246 publications
(633 reference statements)
1
11
0
Order By: Relevance
“…43 We also observed polymer-diABZI uptake by DCs, professional antigen presenting cells that can prime antitumor T cell responses, as well as granulocytes that may also promote antitumor immunity in response to STING activation (Figure 4F-H, S14). 44,45,46 Consistent with their relatively poor capacity for endocytosis, we did not observe uptake by T cells; this may reflect an additional advantage of SAPCon over free diABZI since T cells are susceptible to STING-induced apoptosis.…”
Section: Evaluation Of Sapcon Pharmacokinetics Biodistribution and Ce...supporting
confidence: 66%
“…43 We also observed polymer-diABZI uptake by DCs, professional antigen presenting cells that can prime antitumor T cell responses, as well as granulocytes that may also promote antitumor immunity in response to STING activation (Figure 4F-H, S14). 44,45,46 Consistent with their relatively poor capacity for endocytosis, we did not observe uptake by T cells; this may reflect an additional advantage of SAPCon over free diABZI since T cells are susceptible to STING-induced apoptosis.…”
Section: Evaluation Of Sapcon Pharmacokinetics Biodistribution and Ce...supporting
confidence: 66%
“…Additionally, GO and KEGG gene enrichment analyses suggested that IMPDH1 was associated with neutrophil-related innate immunity and FC gamma R mediated phagocytosis in HCC. As innate immune cells, neutrophils promotes tumor progression by regulating the expression of various inflammatory factors and influencing phagocytosis ( 53 ). Targeting or manipulating neutrophils may gain clinical benefits and are expected to be combined with immunotherapy ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to harness the activity of neutrophils to halt tumor progression, promote elimination of cancer cells, or both could provide clinicians with potent therapies with fewer toxicities than those associated with current interventions. Behrens et al 17…”
Section: Neutrophil S In the S E T Ting Of Malig Nan C Ymentioning
confidence: 99%
“…The ability to harness the activity of neutrophils to halt tumor progression, promote elimination of cancer cells, or both could provide clinicians with potent therapies with fewer toxicities than those associated with current interventions. Behrens et al 17 review how neutrophils and monoclonal antibodies can support antibody‐directed cellular cytotoxicity. With tumor cells covered by tumor‐specific monoclonal antibodies, neutrophils can drive tumor killing.…”
Section: Neutrophils In the Setting Of Malignancymentioning
confidence: 99%
See 1 more Smart Citation